Usability Test Dengan Metode Eye Tracking Pada Website E- Learning Universitas Medan Area - Anangjasa, Trinaldo Sihotang; Sutrisno, Sutrisno; Silviana, Nukhe Andri (INCODING: Journal of Informatics and Computer Science Engineering, 2024)
University of Medan Area (UMA) is one of the universities having an E-learning website for facilitating the teaching and learning process between students and lecturers that can be done remotely and connected via the internet. The features  on  the  UMA  E-Learning  website  are  pretty  complete,  but  still,  the  operation  of  some  features  is  quite complicated  and  time-consuming,  so  some  UMA  students  found  it  hard  to  use  UMA  E-Learning.  The  University  of Medan Area E-Learning website needed to be tested for usability with Elements of Effectiveness and Efficiency. This study aimed to know the usability test results on the University of Medan Area E-Learning website and to know how the proposed improvements to the University of Medan Area E-Learning website. This research used the Eye Tracking method. Eye Tracking is a technique that allowed academics or researchers to analyze visual attention by detecting where users are looking, how long they are looking and the order in which they are looking. This test was carried out by giving several tasks to be done by the respondents, to find out the success and time of the respondents' work. The results in this study was based on the calculation of the effectiveness level in Task 1 obtained a percentage of 88.57%, Task 2 obtained 41.63%, and Task 3 obtained 48.57%. Based on the calculation of the efficiency level, it obtained TBE Task  1  =  0.038  goals/sec.  TBE  Task  2  =  0.024  goals/sec,  TBE  Task  3  =  0.031  goals/sec  and  obtained  ORE  Task  1  = 85.99%, ORE Task 2 = 29.83%, ORE Task 3 = 34.44%.